Cross-field mobility in a pure electron plasma - Emily C. Fossum; Lyon B. King (Вопросы атомной науки и техники, 2006)
An electron trapping apparatus was constructed in order to study electron dynamics in the defining electric and
magnetic fields of a Hall-effect thruster. The approach presented here decouples the cross-field mobility from plasma
effects by conducting measurements on a pure electron plasma in a highly controlled environment. Dielectric walls are
removed completely eliminating all wall effects; thus, electrons are confined solely by a radial magnetic field and a
crossed, independently-controlled, axial electric field that induces the closed-drift azimuthal Hall current. Electron
trajectories and cross-field mobility were examined in response to electric and magnetic field strength and background
neutral density. Для исследования динамики электронов в ведущих электрическом и магнитном полях ускорителя с эффектом Холла было разработано устройство для запирания электронов. Представленный здесь подход подразумевает разделение поперечной подвижности и плазменных эффектов за счёт измерений проводимости в чисто электронной плазме в строго контролируемых внешних условиях. Влияние стенки полностью исключается путём удаления диэлектрических стенок; таким образом электроны удерживаются только радиальным магнитным полем и независимо изменяемым скрещенным аксиальным электрическим полем, которое индуцирует азимутальный ток Холла с замкнутым дрейфом. Выяснялись зависимости траекторий электронов и поперечной подвижности от напряжённости электрического и магнитного полей и фоновой плотности нейтралов. Для дослідження динаміки електронів в ведучих електричному і магнітному полях прискорювача з ефектом Хола був розроблений пристрій для запирання електронів. Підхід, що подається, припускає розділення поперечної рухомості і плазмових ефектів за рахунок вимірювань провідності в чисто електронній плазмі зі строгим контролем зовнішніх умов. Вплив стінки виключається повністю завдяки віддаленню діелектричних стінок; тим самим електрони утримуються тільки радіальним магнітним полем і схрещеним аксіальним електричним полем, яке змінюється незалежно і збуджує азимутальний струм Хола із замкненим дрейфом. З’ясовувалися залежності траєкторій електронів і поперечної рухомості від напруженості електричного і магнітного полів та фонової густини нейтралів.